2013
DOI: 10.1128/aem.00054-13
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Extended-Spectrum β-Lactamase- and Carbapenemase-Producing Enterobacteriaceae Isolates from Rivers and Lakes in Switzerland

Abstract: One of the currently most relevant resistance mechanisms in Enterobacteriaceae is the production of enzymes that lead to modern expanded-spectrum cephalosporin and even carbapenem resistance, mainly extended-spectrum ␤-lactamases (ESBLs) and carbapenemases. A worrisome aspect is the spread of ESBL and carbapenemase producers into the environment. The aim of the present study was to assess the occurrence of ESBL-and carbapenemase-producing Enterobacteriaceae and to further characterize ESBL-and carbapenemase-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
163
3
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(185 citation statements)
references
References 39 publications
(39 reference statements)
8
163
3
4
Order By: Relevance
“…Water certainly promotes the circulation of Enterobacteriaceae strains (be they resistant or not). [18][19][20][21][22][23][24][25] Moreover, access to drinking water is not properly insured in many parts of the city. As such, Enterobacteriaceae from stools can easily affect many people through contaminated water.…”
Section: Discussionmentioning
confidence: 99%
“…Water certainly promotes the circulation of Enterobacteriaceae strains (be they resistant or not). [18][19][20][21][22][23][24][25] Moreover, access to drinking water is not properly insured in many parts of the city. As such, Enterobacteriaceae from stools can easily affect many people through contaminated water.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, bacterial pathogens are assumed to acquire resistance traits from the environment via horizontal gene transfer (Aminov, 2009;Martinez, 2009a). Moreover, various studies have demonstrated that wastewater and animal waste contain large numbers of resistant bacteria, which can pass through the wastewater treatment plant (WWTP) and reach the receiving water bodies (Teuber, 2001;Kü mmerer, 2004;Jury et al, 2011;Rizzo et al, 2013;Zurfluh et al, 2013). There is growing concern that continuous discharge of these contaminants may, at least locally, lead to an increase in the natural resistance background levels and thus enhance the likelihood of antibiotic-resistance genes (ARGs) being transferred back to human and animal commensals or even pathogens (Kim and Aga, 2007;Martinez, 2009b;Cantas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The filters were incubated for 24 hours at 44.5 ℃ in 10 mL of Enterobacteria Enrichment Broth (Haibo, Qingdao, China). One loopful of each of the enrichment cultures was inoculated onto chromogenic Brilliance ESBL agar (Oxoid, Hampshire, UK) to select for ESBL-producers [5,19,20]. All suspected ESBLproducing bacteria were re-selected by MacConkey agar containing cefotaxime 64 mg/mL (Haibo, Qingdao, China) [11].…”
Section: Isolation and Identification Of Esbl-tcmentioning
confidence: 99%
“…It is believed that drug resistant bacteria from humans and animals, discharged into water bodies, could result in the spread of resistance genes within the bacterial community [3][4][5][6][7]. Therefore, the persistence of antibiotic-resistant intestinal bacteria in water environments, particularly extended-spectrum β-lactamase (ESBL)-producing bacteria, could elicit an important public health risk [8,9].…”
Section: Introductionmentioning
confidence: 99%